RE-DYEING PROCESS ON CABRETTA SHEEPSKIN GOLF GLOVES TO IMPROVE COLOR FASTNESS USING ALIPHATIC POLYAMINE DERIVATE AS FIXING AGENT - Wahyu Fajar Winata; Dwi Ari Setyorini; Nur Mutia Rosiati; Fauzi Ashari (Politeknik ATK Yogyakarta, 2024)
This research aims to improve the color fastness of sheep Cabrera golf gloves during the post-tanning process. The post-tanning process includes aging, sammying, shaving, wetting back, re-tanning I, neutralization I, surface dyeing, fixation I, top dyeing, fixation II, neutralization II, fatliquoring, and top fatliquoring. Fastness skin color can be repaired by reprocessing the dyeing process. The raw material used is three sheets of crust-dyed sheep cabretta article of reject quality with a thickness of 0.5-0.55 mm. The chemicals used in the research were H₂O, Foryl PKN, Ammonia, Nexopol AM, Nexopol LA, Formic Acid (FA), Busan 30WB, and Dermafix P Liquid. The post-tanning process using FC fixing material produces crust-dyed sheep cabretta articles with a high color fading, and the finished leather has low rubbing resistance. The test results on crust-dyed skin samples showed that the fading that occurred was very high in the sweat solution, indicated by the solution's color following the sample's color. Reprocessing using Dermafix P Liquid reduced color fading in the sweat solution. On finished leather, dry and wet rubbing resistance was increased to a value of 5 for dry rubbing and a value of 4 for wet rubbing after reprocessing using Dermafix P Liquid, where previously the dry fastness value was 3, and the damp fastness value was 2 in the initial sample. Based on the results obtained, it can be concluded that reprocessing by replacing fixation materials and adding other necessary ingredients can produce leather of better quality and by SNI standards.